Analytical model of the pedagogy of the oppressed systematization of the Paulo Freire’s method - Rodrigues Ramalho, Ramon (2022)
This Article describes the characteristic elements of the Pedagogy of the Oppressed, highlighting the central pedagogical mediations involved in the so-called Paulo Freire?s Method, which is systematized as an Analytical Model in the end of the text. To do so, we have focus on the socio-pedagogical experiences developed by social movements, understanding them as strategies of formation. The study presented here is the result of more than fifteen years of academic investigation along with social movements from Brazil and Argentina. From this perspective, we conducted a bibliographic review of Freire´s central work, Pedagogy of the Oppressed, presented here into two parts: the Complex of the Oppressed and the Dialogical Circuit, as a synthetic reading we offer of Freire´s pedagogical proposal. Our objective is to develop a more comprehensive knowledge about these formation processes, promoting the educational experiences of the social movements and to spread Paulo Freire´s thinking.